Pete the cat screams for ice cream! - Dean, Kim, 1969-; Dean, James, 1957- (Pete the cat., 2024)
I scream! You scream! Pete screams for ice cream! The Just Chillin' ice cream truck is coming today and Pete the Cat can't wait. He runs as fast as he can to find the truck. It's getting late, but his friends need his help. Will Pete take a little time out of his day to help his friends?